The gains of ignoring risk: Insurance with better informed principals - Laura Abrardi; Luca Colombo; Piero Tedeschi (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2019)
We study a competitive insurance market in which insurers have an imperfect informative advantage over policyholders. We show that the presence of insurers privately and heterogeneously informed about risk can explain the concentration levels, the persistent profitability and the pooling of risk observed in some insurance markets. Furthermore, we find that a lower market concentration may entail an increase in insurance premia.
Keywords: D43; D82; G22; 330; Insurance markets; Asymmetric information; Risk assessment; Market concentration